(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Objective: This study aimed to assess the perceived outcome and knowledge of quality antenatal care among nursing mothers attending Olabisi Onabanjo University Teaching Hospital (OOUTH) in Sagamu, Ogun State, Nigeria.